PENGARUH GAYA HIDUP DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE APPLE MELALUI CITRA MEREK SEBAGAI VARIABEL MEDIASI DI KOTA PEKANBARU - , Jushermi, Bellia Bai Azzah , H. Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Along with the needs of the community in the use of smartphones that are increasing making people's buying interest in smartphones is increasing, this is due to the impact of the era of globalization that brings many changes in human life, especially in the field of technology. These changes help people to do things effectively and efficiently. Smartphone is a mobile phone that has a high level of capability and mem; unyai fungwsi similar to a computer. Some people consider a smartphone to be a phone that has advanced features and works using the entire operating system software that provides standard and fundamental relationships for application developers. Therefore, this study will discuss about the influence of lifestyle and brand equity on the purchase decision of apple smartphone products through brand image as a mediation variable in the city of Pekanbaru. The number of respondents in this study was 120 people with sampling methods using Non Probability Sampling techniques by means of accidental sampling (accidental sampling). The method of analysis used in this study is Structural Equation Modelling-Partial Least Square (SEM-PLS). The results obtained are lifestyle variables and brand equity affect the brand image and purchasing decisions of Iphone products in the city of Pekanbaru. Then the brand image mediates the influence of lifestyle and brand equity on the purchase decision of Iphone products in the city of Pekanbaru. Keywords: lifestyle, brand equity, brand image, purchasing decision